Transition of Care Practices from Emergency Department to Inpatient: Survey Data and Development of Algorithm - Lee, Sangil; Jordan, Jaime; Hern, Gene; Kessler, Chad; Promes, Susan; Krzyzaniak, Sarah; Gallahue, Fiona; Stettner, Ted; Druck, Jeffrey (The western journal of emergency medicine, 2017)
We aimed to assess the current scope of handoff education and practice among resident physicians in academic centers and to propose a standardized handoff algorithm for the transition of care from the emergency department (ED) to an inpatient setting. This was a cross-sectional survey targeted at the program directors, associate or assistant program directors, and faculty members of emergency medicine (EM) residency programs in the United States (U.S.). The web-based survey was distributed to potential subjects through a listserv. A panel of experts used a modified Delphi approach to develop a standardized algorithm for ED to inpatient handoff. 121 of 172 programs responded to the survey for an overall response rate of 70.3%. Our survey showed that most EM programs in the U.S. have some form of handoff training, and the majority of them occur either during orientation or in the clinical setting. The handoff structure from ED to inpatient is not well standardized, and in those places with a formalized handoff system, over 70% of residents do not uniformly follow it. Approximately half of responding programs felt that their current handoff system was safe and effective. About half of the programs did not formally assess the handoff proficiency of trainees. Handoffs most commonly take place over the phone, though respondents disagree about the ideal place for a handoff to occur, with nearly equivalent responses between programs favoring the bedside over the phone or face-to-face on a computer. Approximately two-thirds of responding programs reported that their residents were competent in performing ED to inpatient handoffs. Based on this survey and on the review of the literature, we developed a five-step algorithm for the transition of care from the ED to the inpatient setting. Our results identified the current trends of education and practice in transitions of care, from the ED to the inpatient setting in U.S. academic medical centers. An algorithm, which guides this process, is proposed to address the current gap in the standardized approach to ED to inpatient handoffs that were identified in the survey's assessment of needs.